Myocardial performance is impaired in cardiac amyloidosis: role of myocardial work-derived parameter in differential diagnosis with phenocopies and prognostic implications. (14th October 2021) - Palmiero, G; Rubino, M; Monda, E; Caiazza, M; Di Fraia, F; Lioncino, M; Vetrano, E; Dongiglio, F; Cerciello, G; Manganelli, F; Ascione, L; Caso, P; et al.
Abstract: Background: Cardiac amyloidosis (CA) is an infiltrative disorder characterized by left ventricular (LV) thickening and dysfunction. Due to it poor prognosis its early detection and differential diagnosis among other forms of cardiomyopathies is fundamental. Purpose: This study aimed to compare the diagnostic accuracy of LV classical and and novel echocardiographic parameters in differentiating CA from other forms of genetic and non-genetic cardiomyopathies with hypertrophic phenotype. Methods: We included 50 patients with CA (26 pts with AL and 24 pts with wild type ATTR form) and 75 patients with LV hypertrophy (LVH) [25 patients with hypertrophic cardiomyopathy (HCM), 25 with hypertensive cardiomyopathy (HypCM), and 25 with aortic stenosis (AS)]. Besides routine echocardiographic measurements, we analysed standard and novel echo parameters implied in LV assessment [LV ejection fraction (LVEF), myocardial contraction fraction (MCF), global longitudinal strain (GLS), relative regional strain ratio (RRSR), ejection fraction on strain ratio (EFSR)], included novel Myocardial Work (MW) parameters [Global Work Index (GWI), Global Constructive Work (GCW), Global Wasted Work (GWW), Global Work Efficiency (GWE)]. Results: Patients in CA group showed a smallest LV cavity size, higher LV mass and, consequently, a more pronounced concentric hypertrophy compared to LVH group. All LV systolic parameters where more impaired in CA than in LVH group. At ROC curve analysis, among all others, GCW showed the best performance in discriminating CA from LVH (AUC 0.886; 95% CI: 0.819–0.954; P<0, 0001), with a cut-off value <1473 mmHg% showing good sensitivity and specificity (90% and 82%, respectively). At linear regression analysis GCW correlated with IVSD (P<0, 0001), PWD (p<0, 0001), RWT ratio (p<0, 0001), LVMi (p<0, 0001), MCF (P<0, 0001), LVESV (p<0, 002), LVEF (P<0, 0001), EFSR (p<0, 0001) and RRSR (p<0, 0001). At multivariate analysis, PWD (P<0, 029) and RWT ratio (p<0, 014) were the only parameters associated. At 24 months follow-up there were 15 deaths in the CA group and 4 in LVH group. At Kaplan-Meier analysis the overall survival free of cardiovascular death was reduced in the lowest GCW interquartile ranges (log-rank χ 2 21, 5; p<0, 0001). At Cox hazard ratio analysis GCW (β 1, 233; 95% CI: 1, 201–1, 246; P<0, 0001) was the only prognostic parameter associated with cardiovascular mortality. Discussion: Although CA and and LVH have with similar phenotype, they differ greatly in terms of systolic function. The MW, estimated by non-invasive pressure-strain loops, is a novel method for a load-independent LV systolic function assessment. In the present study the GCW showed the best ability in detecting CA in comparison to other parameters usually implied in clinical practice. Conclusion: Myocardial performance is significantly reduced in CA compared to other forms of LVH. GCW showed to be a promising novel diagnostic and prognostic factor in this setting. Funding Acknowledgement: Type of funding sources: None.